DEVELOPING CRITICAL THINKING SKILL THROUGH E-LEARNING: A CASE STUDY AT MUHAMMADIYAH UNIVERSITIES IN INDONESIA - Shodiq, Sadam Fajar; Kurniati, Yunia (International Journal of Psychosocial Rehabilitation, 2020)
Critical thinking skill is one of the abilities that must be possessed by students as agents of change in order to be able to maintain their existence in the era of the industrial revolution 4.0, but not a few of them are less able to develop and improve it. In an increasingly sophisticated age, e-learning is clear evidence of digitalization that has spread to all dimensions of life, not least in the scope of education. E-learning is a learning system that is relevant to the times, and with features available in e-learning, it is expected to be able to increase students' critical thinking. The focus of this research was to examine how much influence of the e-learning system in Muhammadiyah University on improving the critical thinking skills of its students. This research used a quantitative approach, with the type of survey research. Data were collected using questionnaires, interviews, and documentation. The data analysis used descriptive statistical tests and simple linear regression tests. The results of his research were: (1) The implementation of e-learning systems in Muhammadiyah Universities could be classified as moderate, with a percentage of 45.5%. (2) The level of critical thinking skills of Muhammadiyah University students could be categorized as moderate, with a percentage of 60.7%. (3) The results of the data analysis showed that the value of sig, 0,000